2016
DOI: 10.1016/j.appet.2016.02.015
|View full text |Cite
|
Sign up to set email alerts
|

Functional Imagery Training to reduce snacking: Testing a novel motivational intervention based on Elaborated Intrusion theory

Abstract: Functional Imagery Training (FIT) is a new theory-based, manualized intervention that trains positive goal imagery. Multisensory episodic imagery of proximal personal goals is elicited and practised, to sustain motivation and compete with less functional cravings. This study tested the impact of a single session of FIT plus a booster phone call on snacking. In a stepped-wedge design, 45 participants who wanted to lose weight or reduce snacking were randomly assigned to receive a session of FIT immediately or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 102 publications
(54 citation statements)
references
References 37 publications
2
52
0
Order By: Relevance
“…Vealey and Greenleaf (2001) define imagery as "using all the senses to recreate or create an experience in the mind" (p. 248), and motivational imagery focuses on a goal orientated approach. Combining the need to develop a novel intervention through goal-centered motivation, this study tests the potential for Functional Imagery Training (FIT) (Andrade, Khalil, Dickson, May, & Kavanagh, 2016) as a way to develop character, precisely; grit. Andrade et al, (2016) developed FIT as a client-centered approach "that creates a context where people are encouraged to consider the utility and possibility of functional behaviour change" (p. 259).…”
Section: Fit For Soccermentioning
confidence: 99%
See 2 more Smart Citations
“…Vealey and Greenleaf (2001) define imagery as "using all the senses to recreate or create an experience in the mind" (p. 248), and motivational imagery focuses on a goal orientated approach. Combining the need to develop a novel intervention through goal-centered motivation, this study tests the potential for Functional Imagery Training (FIT) (Andrade, Khalil, Dickson, May, & Kavanagh, 2016) as a way to develop character, precisely; grit. Andrade et al, (2016) developed FIT as a client-centered approach "that creates a context where people are encouraged to consider the utility and possibility of functional behaviour change" (p. 259).…”
Section: Fit For Soccermentioning
confidence: 99%
“…Combining the need to develop a novel intervention through goal-centered motivation, this study tests the potential for Functional Imagery Training (FIT) (Andrade, Khalil, Dickson, May, & Kavanagh, 2016) as a way to develop character, precisely; grit. Andrade et al, (2016) developed FIT as a client-centered approach "that creates a context where people are encouraged to consider the utility and possibility of functional behaviour change" (p. 259). FIT pairs the spirit of Motivational Interviewing (MI) (Miller & Rollnick, 2012) with a focus upon enhancing the concreteness and vividness of an individual's goal-related mental imagery.…”
Section: Fit For Soccermentioning
confidence: 99%
See 1 more Smart Citation
“…One area of research where this approach might be particularly relevant is the promotion of sustainable eating habits (e.g., reducing meat consumption, buying local food). Research has shown that through practicing positive goal imagery individuals can change their eating behaviors toward a healthier lifestyle (Andrade et al, 2016) – a similar approach could be used to work toward a more sustainable lifestyle.…”
Section: Program Of Researchmentioning
confidence: 99%
“…Participants allocated to the cue‐monitoring group reported significantly fewer unhealthy snacking situations per day than the controls (1.49 situations, SD 0.75 vs. 1.84 situations, SD 0.82). In another short‐term intervention study using functional imagery training (a method similar to motivational interviewing but focused on mental imagery exercises for achieving goals) found lower snacking intake over a 2‐week period compared to a waiting list control . Experimental studies, mostly involving university students, have also shown that social norm and health messages given prior to ad libitum snacks are associated with less energy intake .…”
Section: Introductionmentioning
confidence: 99%